2020
DOI: 10.1021/acs.jpcc.0c00307
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Structural Transformation in γ′-Fe4N and GeNFe3

Abstract: Ge-substitution dependence of the structural, electronic, and magnetic properties for Ge x NFe 4−x (0.0 ≤ x ≤ 1.0) compounds has been investigated systematically. An obvious structural phase transition from Pm3m to I4/mcm around x = 0.5 is observed by substitution-dependent X-ray diffractions. The modified lattice constants a′ = a/2 1/2 and c′ = c/2 are used to depict the specific structure for tetragonal GeNFe 3 . Especially, the tetragonal structure exhibits an expansion along the direction of the c axis com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…The diffraction patterns can be well satisfied by corresponding Pm 3 m and I 4/ mcm with reliable fitting parameters ( R p , R wp , and χ 2 ), indicating that our samples are good in quality. The refined lattice parameters ( a = 3.8949 Å for cubic SnNFe 3 ; a = 5.3052 Å, c = 7.7539 Å for tetragonal phase GeNFe 3 ) by using the standard Rietveld technique are quite agreement with other previous reports 14,15 …”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The diffraction patterns can be well satisfied by corresponding Pm 3 m and I 4/ mcm with reliable fitting parameters ( R p , R wp , and χ 2 ), indicating that our samples are good in quality. The refined lattice parameters ( a = 3.8949 Å for cubic SnNFe 3 ; a = 5.3052 Å, c = 7.7539 Å for tetragonal phase GeNFe 3 ) by using the standard Rietveld technique are quite agreement with other previous reports 14,15 …”
Section: Resultssupporting
confidence: 90%
“…Now, we begin to discuss the observed structure transition; in reverse, the cubic structure (Pm3m) cannot support the shrinking lattice, and thus, tetragonal structure (I4/mcm) appears in Ge 1−x Sn x NFe 3 around the critical dopants x around the interval 0.4−0.5. 15 The insets of spatial diagram in Figure 2 give the detailed structural category for GeNFe 3 and SnNFe 3 , and this result is completely consistent with the developing progress of lattice characteristics. And likewise, this observed structural transition is similar to the previous investigation of GaCFe 3−x Co x , 17 which is also resulted from the collapsed structure.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…[14][15][16] Scholz and Dronskowski 17 found that the structure of Fe 4−x Ge x N y changes from a cubic antiperovskite structure to the distorted tetragonal structure with increasing content of Ge replacing Fe. Liu and coworkers showed that this transition is con-tinuous as a function of Ge content in Fe 4−x Ge x N. 18 In any case, Fe 3 GeN, which shows a net magnetic moment 0.2-0.3 µ B /Fe with sample dependence, has tetragonal symmetry at room temperature. 17,19 This structure has a doubled primitive unit cell containing two formula units, space group I4/mcm, number 140.…”
Section: Introductionmentioning
confidence: 98%